Evaluation about Self-Care of the Patients with Endometriosis - Šakinytė, Ieva; Šakalytė, Danguolė (Slauga. Mokslas ir praktika, 2023)
Abstract. Endometriosis is a chronic, estrogen-dependent, incurable gynecological disease, the causes of which are still unclear. One of the most important factors in proper disease control is patient involvement in self-care. Well-directed self-care can help reduce the symptoms and damage caused by endometriosis. Aim. To evaluate the self-care of patients with endometriosis. A quantitative research was conducted, using a survey. The research was conducted on the Internet, on the social platform Facebook, in the endometriosis group. During the study, 70 adult women of childbearing age (18–49 years) with endometriosis were surveyed. 64 questionnaires were selected for data analysis. For descriptive statistics, percentage distribution of data is used. The rank and interval scales are used for analytical statistics. The Chi-square (χ²) criterion and a statistical significance of p<0.05 were used for the correlation between two attributes. Results and conclusions. A higher proportion of respondents do not use any self-care at all, and a statistically significant effect was found between duration of illness and use of self-care. The longer the duration of illness, the less self-care is used. It also found that the most effective self-care interventions are heat applications, nutrition and phytotherapy, while the least effective are yoga and psychotherapy. The study showed that self-care is insufficient in the management of endometriosis and its symptoms.